2019
DOI: 10.1155/2019/9740475
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value Investigation and Bioinformatics Analysis of miR-31 in Patients with Lymph Node Metastasis of Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the most frequent cancers occurring in developed countries. Distant CRC metastasis causes more than 90% of CRC-associated mortality. MicroRNAs (miRNAs) play a key role in regulating tumor metastasis and could be potential diagnostic biomarkers in CRC patients. This study is aimed at identifying miRNAs that can be used as diagnostic biomarkers for CRC metastasis. Towards this goal, we compared the expression of five miRNAs commonly associated with metastasis (i.e., miR-10b, miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
(43 reference statements)
2
15
0
Order By: Relevance
“…To elucidate the potential mechanism of miR-31-5p involvement in COAD, a computational target prediction was performed, which identified a pivotal miR-31-5p target gene, TNS1, which is downregulated in COAD patients and closely correlated with COAD progression. This is consistent with a recent study that found that TNS1 level was negatively correlated with miR-31 in COAD tumor tissues [31]. TNS1 is a key component of specialized cellular adhesions that bind to extracellular fibronectin fibrils [32].…”
Section: Agingsupporting
confidence: 93%
“…To elucidate the potential mechanism of miR-31-5p involvement in COAD, a computational target prediction was performed, which identified a pivotal miR-31-5p target gene, TNS1, which is downregulated in COAD patients and closely correlated with COAD progression. This is consistent with a recent study that found that TNS1 level was negatively correlated with miR-31 in COAD tumor tissues [31]. TNS1 is a key component of specialized cellular adhesions that bind to extracellular fibronectin fibrils [32].…”
Section: Agingsupporting
confidence: 93%
“…Consistent with the report above, our results in this study also discovered that miR-31 was high-expressed in CRC tissues. What's more, miR-31 is proved to be correlated to the metastasis of CRC and can regulate autophagy, proliferation, and chemoresistance of CRC cells (16,29,30). Similarly, in this study, the results con rmed that miR-31 overexpression not only promoted the migration, invasion, and suppressed the apoptosis of CRC cells but also counteracted the effect of circ_0026344.…”
Section: Discussionsupporting
confidence: 74%
“…In particular, circ-ITGA7 inhibits the proliferation of CRC cells by sponging miR-3187-3p (14), circ_0009361 acts as a sponge of miR-582 to inhibit the processes of CRC (8), circ_0000523 modulates the proliferation and apoptosis of CRC cells through acting as a sponge of miR-31 (13). MiR-31, highly expressed in CRC, is widely proved that it is correlated to the metastasis of CRC and has a high value in CRC diagnosis (15,16). Whether circ_0026344 had an effect on CRC by sponging miR-31 needs further exploration and veri cation.…”
mentioning
confidence: 99%
“…TNS1 negatively regulates tumour migration and invasion, and its high expression is associated with longer metastasis-free survival in breast cancer [ 56 ]. Moreover, higher expression of TNS1 is associated with worse prognosis in colon adenocarcinoma [ 57 ]. In this study, we observed that TNS1 was downregulated in LUAD tissues and that higher expression was associated with better prognosis ( Figure 9(d) ).…”
Section: Resultsmentioning
confidence: 99%